2017
DOI: 10.1186/s41043-017-0085-1
|View full text |Cite|
|
Sign up to set email alerts
|

Utilization of health facilities and predictors of health-seeking behavior for under-five children with acute diarrhea in slums of Addis Ababa, Ethiopia: a community-based cross-sectional study

Abstract: BackgroundInformation on health-seeking behavior and utilization of health facilities in slums of Addis Ababa is scarce, impeding the implementation of effective interventions. The purpose of this study is to assess the status of health facilities utilization and predictors for health-seeking behavior of mothers/caregivers of under-five children with acute diarrhea in slums of Addis Ababa, Ethiopia.MethodsA community-based cross-sectional study design was employed in five rounds of surveys in seven kebeles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
88
5
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(108 citation statements)
references
References 38 publications
13
88
5
2
Order By: Relevance
“…Those mothers who have more than or equal to two number of under-five children in the family members were 40% less likely to seek medical care than those who have one under-five child in family members, contrary to our finding, study done in Addis Ababa indicated that there was no difference in health care seeking behavior of mothers/caregivers of under-five children with acute diarrhea due to number of under-five children in the family (20). This might be due to the incapability of the mothers/caregivers to care for many under-five children and a shortage of money for seeking care in the study area as compared to Addis Ababa mothers/caregivers.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Those mothers who have more than or equal to two number of under-five children in the family members were 40% less likely to seek medical care than those who have one under-five child in family members, contrary to our finding, study done in Addis Ababa indicated that there was no difference in health care seeking behavior of mothers/caregivers of under-five children with acute diarrhea due to number of under-five children in the family (20). This might be due to the incapability of the mothers/caregivers to care for many under-five children and a shortage of money for seeking care in the study area as compared to Addis Ababa mothers/caregivers.…”
Section: Discussioncontrasting
confidence: 99%
“…The magnitude of health care seeking behavior of this study was higher than the study conducted at the national level of Ethiopia (56%) (18), and in Addis Abeba (56.6%) (20). This difference might be due to seasonal variation.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Before data analysis, data were cleaned using two steps as described elsewhere [45]. Descriptive statistics [n (%)] were carried out for cases and controls, including means (±SD (standard deviations) for continuous variables.…”
Section: Methodsmentioning
confidence: 99%
“…Seeking appropriate and prompt care could reduce by 20 percent of childhood deaths due to illnesses and prevent long-term complication [5]. However, health care seeking behavior of mothers of under-five children was poor in Ethiopia and only a small proportion of under-five children receive appropriate care timely [7][8][9][10]. Accordingly, EDHS 2016 revealed that only 44% of under-five children with diarrheal diseases were taken for advice or treatment to a health facility.…”
Section: Introductionmentioning
confidence: 99%